2015
DOI: 10.1021/acs.biochem.5b00659
|View full text |Cite
|
Sign up to set email alerts
|

Binuclear CuA Formation in Biosynthetic Models of CuA in Azurin Proceeds via a Novel Cu(Cys)2His Mononuclear Copper Intermediate

Abstract: CuA is a binuclear electron transfer (ET) center found in cytochrome c oxidases (CcOs), nitrous oxide reductases (N2ORs), and nitric oxide reductase (NOR). In these proteins, the CuA centers facilitate efficient ET (kET > 104 s−1) under low thermodynamic driving forces (10–90 mV). While the structure and functional properties of CuA are well understood, a detailed mechanism of copper incorporation into the protein and the identity of the intermediates formed during the CuA maturation process are still lacking.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…More precisely, the energy that is required for two S-Ni-L fragments to adopt to the transition state geometry is expected to benefit from diverging stereoelectronic properties of the nickel ions. This proposal explains the marked kinetic preference of formation of sulphur-bridged [Ni 2 (µ-S) 2 ] + , Ni = Ni(I)/Ni(II), from geometrically independent, heterovalent nickel sites, and augments mechanistic data reported for the skeletal assembly of Cu A [1, [6][7][8][9]. This mechanism may also apply to the self-assembly of the mixed-valent form of 2Fe-ferredoxins, for which, however, experimental…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…More precisely, the energy that is required for two S-Ni-L fragments to adopt to the transition state geometry is expected to benefit from diverging stereoelectronic properties of the nickel ions. This proposal explains the marked kinetic preference of formation of sulphur-bridged [Ni 2 (µ-S) 2 ] + , Ni = Ni(I)/Ni(II), from geometrically independent, heterovalent nickel sites, and augments mechanistic data reported for the skeletal assembly of Cu A [1, [6][7][8][9]. This mechanism may also apply to the self-assembly of the mixed-valent form of 2Fe-ferredoxins, for which, however, experimental…”
Section: Discussionsupporting
confidence: 63%
“…Whereas the understanding of the relationship between biological function and electronic properties of closed-and open-shell forms of Cu A and 2Fe-ferredoxins has been widely developed, details on the mechanism of formation and of the parameters that control structural persistence of [M 2 (µ-S) 2 ] sites have remained largely unknown. In vitro studies starting from an apoprotein concluded that Cu A assembles rapidly in form of its open-shell state after stepwise introduction of Cu(I) and Cu(II) sites [6][7][8][9]. Different from natural Cu A , preparative assembly of the bimetallic core [Cu 2 (µ-S) 2 ] commonly involves dimerization of homovalent precurors [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Although the structure of Cu A and its biological functions are well‐known, the incorporation of copper in the proteins and, in particular, the formation of the mixed‐valent dinuclear centre is one of the remaining challenges in understanding Cu A . This assembly proceeds through several different types of mononuclear copper centres, and a new intermediate Cu(Cys) 2 His complex has been identified recently …”
Section: Introductionmentioning
confidence: 99%
“…Their propensity to self‐assemble spontaneously has not only been utilized to prepare [2M‐2S] structures of Fe and Cu synthetically from mononuclear precursors but also appears to play a role in biosynthesis . Quantitative insight into this process is limited to the in vivo/vitro maturation of the Cu A [2Cu‐2S] + site either in an apoprotein or models thereof . Notably, one electron reduction of [2Fe‐2S] 2+ cores triggers self‐assembly into [4Fe 2.5+ ‐4S] 2+ .…”
Section: Introductionmentioning
confidence: 99%